Students and Teachers' Perceptions on English Online Teaching-Learning in Sumbawa Island during Covid-19: Challenges and Strategies - Ramdhani, Suciaty; Kholidi, Muhammad Azhar (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims at examining students and teachersâ€™ perceptions on problems and solutions in online English classrooms during Covid-19 outbreak. This qualitative study reports of four students and four teachers purposefully selected in five junior high schools in Sumbawa Island, West Nusa Tenggara, Indonesia. The data are collected through semi-formal interview. Open coding technique is used for analyzing the text data manually. The findings showed that both the students and the teachers mostly faced internet data and connectivity issues. The teachers also experienced challenges in technology utility and pedagogical aspects such as teaching method and time management, while the students have also struggled in processing the learning input and sometimes were less motivated. All of the participants utilized some ways to deal with internet and connectivity problems, such as finding WI-FI, conducting a blended-learning classroom, and seeking help and support from friends and colleagues. Â Moreover, most of the teachers recommended that the school principal or educational stakeholders take initiatives to train them in instructional technology and competency in teaching. Thus, the implementation of the online learning during the Covid-19 pandemic, especially in rural area, caused various problems for teachers and students, as well as triggered them to seek for the solutions and put their constructive wishes on the schools and educational stakeholder.